Sports-related health problems in para-sports: A systematic review with quality assessment - Luijten, S. C. M.; te Loo, L. M.; Nauta, J.; Janssen, T. W. J.; Holla, J. F. M.; Vriend, I.; Verhagen, E. (Sports Health: A Multidisciplinary Approach, 2024)
Context: Participation in sports is associated with a risk of sports-related health problems. For athletes with an impairment, sports-related health problems further burden an already restricted lifestyle, underlining the importance of prevention strategies in para-sports.